THE EFFECT OF JEOPARDY GAME ON STUDENTS’ READING COMPREHENSION - Astuty Simbolon; Nursia Simanjuntak; Rut Ayzta Pardede; Sarah Gultom; Natalia Widya Pasca Tarigan; Rinci Simbolon (Jurnal Basataka (JBT), 2022)
The problem of this research is does jeopardy game give an effecton reading students’comprehension. This research is conduct for eight-grade SMP Advent 2 Medan in academic year 2021/2022. This quantitative research is experimental research uses pretest, treatment, and post-test design. The population of this study is SMP Advent 2 Medan and samples are 46 students. Data are collected through multiple-choice tests consisting of 20 questions with four options. Jeopardy game contains independent variable of the study, while understanding the students reading is a dependent variable. According to compilation, test result shows the average score of exsperimental group is 100 which is considered very good, and the control group is 95, which is considered very good. Conclusion of this research is using jeopardy game as an effective strategy to enhance the reading of understanding students at SMP Advent 2 Medan.